Hubungan Agama dan Politik: Suatu Refleksi Teologis-Kultural - Stephen Tong (Societas Dei: Jurnal Agama dan Masyarakat, 2014)
ABSTRACT: A belief on absoluteness should not cause disharmony among people with different beliefs; instead it should continue task of peace. Calvinisme anthropology that believes in the existence of truth, justice and holiness in humanity encourages the development of democracy. Common grace for all mandkind propels heart attitude to accept diversity. Mandkind, wich is created as the image of God, reflects spiritual character to worship God.Â KEYWORDS:Â Calvinism, religion, democracy, common grace, nationalism